Willingness to Pay (WTP) for COVID-19 Vaccine Booster Dose and Its Determinants in Indonesia - Harapan Harapan; Malik Sallam; Raisha Fathima; Hendrix Indra Kusuma; Samsul Anwar; Widhy Yudistira Nalapraya; Adityo Wibowo; Ketut Dewi Kumara Wati; Ayunda Medina; Anna Hanifa Defrita; Yesi Astri; Arie Prasetyowati; et al. (MDPI AG, 2022)
Willingness to pay (WTP) for booster doses of coronavirus disease 2019 (COVID-19) vaccines is an under studied research topic. Therefore, the current study aimed to investigate the WTP for the booster doses of COVID-19 vaccines and its predictors in Indonesia using an online survey distributed all over the provinces of this low-middle-income country. The WTP was evaluated using a basic dichotomous contingent valuation approach, and its associated determinants were evaluated using a linear regression model. Out of 2935 responders, 66.2% (1942/2935) were willing to pay for a booster dose of the COVID-19 vaccine. The majority of respondents (63.5%) were willing to pay within a price range of 100,000-500,000 Indonesian rupiah (IDR), i.e., USD 6.71-33.57. Being older than 40 years, having a higher educational level, having a higher income, knowing and understanding that booster doses were important, and having a vaccine status that is certified halal (permissible in Islamic law), were all associated with a higher WTP for the booster dose of COVID-19 vaccines. The study findings imply that the WTP for a booster dose of COVID-19 vaccination in Indonesia is lower compared to acceptance of vaccines provided free of charge. This WTP data can be utilized to develop a pricing scheme for the booster doses of COVID-19 vaccination in the country with potential benefits in other low-income countries. The government may be required to provide subsidies for the herd immunity vaccination process to proceed as anticipated. Furthermore, the public community must be educated on the importance of vaccination as well as the fact that the COVID-19 epidemic is far from being over.